Evaluation of ocular surface disease among cigarette smokers - Soon, Jason Allan Cheah Seng (2023)
Introduction Ocular surface disease (OSD) represents a spectrum of disorders that affect the surface of the eye and dry eye disease is the most common of the OSD. Tobacco smoke is emerging as one of the public health threats in the current world, whether direct or indirect exposure. This can lead to ocular disease such as age-related macular degeneration, thyroid eye disease and ocular surface disease. Objective To evaluate the ocular surface disease parameters among cigarette smokers Methodology A cross-sectional study was conducted in ophthalmology clinic of Hospital Kuala Lumpur and Hospital University Sains Malaysia from Dec 2020 till June 2022. The samples were selected with the convenience purposive sampling method. The participants who fulfilled the inclusion criteria were recruited. Participants were divided into cigarette smoker group and non-cigarette smoker group. The participants in both groups then undergo dry eye assessment such as Ocular Surface Disease Index (OSDI) score, Tear break up time (TBUT), cornea fluorescein staining and Schirmer Introduction Ocular surface disease (OSD) represents a spectrum of disorders that affect the surface of the eye and dry eye disease is the most common of the OSD. Tobacco smoke is emerging as one of the public health threats in the current world, whether direct or indirect exposure. This can lead to ocular disease such as age-related macular degeneration, thyroid eye disease and ocular surface disease. Objective To evaluate the ocular surface disease parameters among cigarette smokers Methodology A cross-sectional study was conducted in ophthalmology clinic of Hospital Kuala Lumpur and Hospital University Sains Malaysia from Dec 2020 till June 2022. The samples were selected with the convenience purposive sampling method. The participants who fulfilled the inclusion criteria were recruited. Participants were divided into cigarette smoker group and non-cigarette smoker group. The participants in both groups then undergo dry eye assessment such as Ocular Surface Disease Index (OSDI) score, Tear break up time (TBUT), cornea fluorescein staining and Schirmer number of cigarette smokes with ocular surface parameters TBUT and cornea fluorescein staining. Therefore, lifestyle change in stopping cigarette smoking can reduce the occurrence of dry eye disease while educating and promoting a behaviour change on cigarette usage among the youths and young adults.